ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATERI SEGIEMPAT BERDASARKAN NEWMAN’S ERROR ANALYSIS (NEA) DITINJAU DARI KECERDASAN LOGIS MATEMATIS SISWA - Trapsilasiwi, Dinawati; Aulia, Kharisma; Sugiarti, Titik (Kadikma, 2018)
This reserach aims to analyze the student error and determine the percentage of student error doing word problems on subject of the quadrilateral based on Newman’s Error Analysis (NEA) viewed from mathematical logic intelligence. This research use a qualitative approach and the type of research is descriptive. Subject in this research are 6 students in class VII H of Junior High School 7 Jember. Data collection was performed by the method of test and interview. There were 7 students who have high mathematical logic intelligence, 21 students who have medium mathematical logic intelligence, and 9 students who have low mathematical logic intelligence. The result of research showed that the error made by students with high mathematical logic intelligence consist 10% reading error, 3,3% comprehension error, 3,3% transformation error, 3,3% process skill error, and 6,7% encoding error. The error made by students with medium mathematical logic intelligence consist 10% reading error, 6,7% comprehension error, 16,7% transformation error, 13,3% process skill error, and 13,3% encoding error. The error made by students with low mathematical logic intelligence consist 13,3% reading error, 13,3% comprehension error, 20% transformation error, 20% process skill error, and 13,3% encoding error. Keywords: Newman’s Error Analysis, word problem, mathematical logic intelligence, quadrilateral.